Validation of an Actuator Line Model Coupled to a Dynamic Stall Model for Pitching Motions Characteristic to Vertical Axis Turbines. Issue 2 (September 2016) - Mendoza, Victor; Bachant, Peter; Wosnik, Martin; Goude, Anders
Abstract: Vertical axis wind turbines (VAWT) can be used to extract renewable energy from wind flows. A simpler design, low cost of maintenance, and the ability to accept flow from all directions perpendicular to the rotor axis are some of the most important advantages over conventional horizontal axis wind turbines (HAWT). However, VAWT encounter complex and unsteady fluid dynamics, which present significant modeling challenges. One of the most relevant phenomena is dynamic stall, which is caused by the unsteady variation of angle of attack throughout the blade rotation, and is the focus of the present study. Dynamic stall is usually used as a passive control for VAWT operating conditions, hence the importance of predicting its effects. In this study, a coupled model is implemented with the open-source CFD toolbox OpenFOAM for solving the Navier-Stokes equations, where an actuator line model and dynamic stall model are used to compute the blade loading and body force. Force coefficients obtained from the model are validated with experimental data of pitching airfoil in similar operating conditions as an H-rotor type VAWT. Numerical results show reasonable agreement with experimental data for pitching motion.